2023
DOI: 10.1002/lary.31044
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Performance of Cochlear Implants in Neurofibromatosis Type 2

Stefanie Seo,
Sarek Shen,
Andy S. Ding
et al.

Abstract: ObjectiveCochlear implants (CIs) are a well‐established treatment modality for hearing loss due to neurofibromatosis type 2 (NF2). Our aim is to investigate variables that affect longitudinal performance of CIs among patients with NF2.Study DesignRetrospective review at a single academic institution consisting of patients who have received cochlear implants following hearing loss due to NF2.MethodsThe primary outcome examined was CI disuse or explantation. Associated clinical and surgical variables were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…55 Explantation of the CI may be considered if it no longer provides auditory benefits, particularly if it causes discomfort, or to prevent MRI artifacts and magnet displacement. 56 ABI should be considered in cases of CI failure and in patients with nonfunctioning cochlear nerves. 57 Indeed, unpublished data from our center showed that (57%) of the 58 NF2 patients with ABI, made use of their implants and that 7 (12%) had a speech intelligibility score with ABI alone ≥40%.…”
Section: Discussionmentioning
confidence: 99%
“…55 Explantation of the CI may be considered if it no longer provides auditory benefits, particularly if it causes discomfort, or to prevent MRI artifacts and magnet displacement. 56 ABI should be considered in cases of CI failure and in patients with nonfunctioning cochlear nerves. 57 Indeed, unpublished data from our center showed that (57%) of the 58 NF2 patients with ABI, made use of their implants and that 7 (12%) had a speech intelligibility score with ABI alone ≥40%.…”
Section: Discussionmentioning
confidence: 99%